ANALISIS KELEMBAGAAN INDUSTRI TEMBAKAU DI EKS - KARESIDENAN BESUKI: PARADIGMA “NEW INSTITUTIONAL ECONOMICS” (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2012)
Tobacco industry become leading sectors of industrial becauase has linkages upstream to downstream industries in Eks-Karesidenan Besuki. The upstream and downstream linkages in the tobacco industry makes an institutional concept of relationship that includes transactions from all economic actors in tobacco industry. This study aims to identify patterns of institutional tobacco industry in Eks-Karesidenan Besuki. This research combines quantitative and qualitative approaches. The study area includes Eks-Karesidenan Besuki like Jember Regency, Situbondo Regency, Bondowoso Regency and Banyuwangi Regency. This study uses primary data. The technique of collecting data using questionnaires and in-depth interviews. The key informant selection with snow ball method. The method of analysis in this study uses the synthesis of Analysis Hierarchy Process (AHP) and Game Theory with descriptive analysis. The analysis showed that the pattern of institution of tobacco industry in the Eks-Karesidenan Besuki tend to be dominated by informal institutions. Informal institutions based on a sense of trust and community similarities of culture in economic transactions of upstream to downstream in the tobacco industry. Business actors believed that informal institution improve the quality of tobacco products and the relationship of culture in society. Business actors also believe the contract which has the legality provide increased bargaining power of all economic actors and avoiding institutional inefficiency.